KAJIAN PEMBUATAN TEH KOMBUCHA DARI KULIT BUAH MANGGIS (Garcinia mangostana L.) - Pratama, Nofiyanto; Pato, Usman; ', Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Mangosteen is a type of tropical fruit.The pulp of mangosteen is usually consumed by the people of Indonesia and the it is feel has not been utilized so far. The purpose of this study was to determine the time of  fermentation to produce tea of mangosteen peel with the best quality and know panelists assessment of the kombucha tea from the peel of the mangosteen. This study used a Completely Randomized Design (CRD) with 5 treatments and 4 replications thus obtaining 20 experimental units). The data obtained were statistically analyzed using Analysis of Variance (Anova). If the F count is greater than or equal to F table then continued with DNMRT test at 5% level. Results of research showed that different fermentation times significantly affected the degree of acidity (pH), antioxidants, sweetness, sourness is descriptive test and assessment of the overall hedonic test. The best formulation of kombucha tea is treatment F1 (fermented for 6 days)  which shows a pH of 3,75, the antioxidants value of 38,61 µg/ml and 324,45 µg/ml of the toxicity value. Keywords: Mangosteen peel, fermentation times, kombucha tea